2020
DOI: 10.12659/msm.920541
|View full text |Cite
|
Sign up to set email alerts
|

GANT61 and Valproic Acid Synergistically Inhibited Multiple Myeloma Cell Proliferation via Hedgehog Signaling Pathway

Abstract: Background: Multiple myeloma is featured by the proliferation of malignant plasma cell in bone marrow. We aimed to demonstrate the effects of valproic acid combined with GANT61 on multiple myeloma cell proliferation and clarify its mechanism. Material/Methods: Multiple myeloma cells were exposed to valproic acid, GANT61, or the combination of valproic acid and GANT61, respectively. MTT assay was performed to detect the cell viability. Quantitative reverse transcriptase polymerase chain reaction and western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…We demonstrated that VPA significantly inhibited the proliferation of HeLa cells in a concentration-and timedependent manner. This finding is consistent with other previous studies indicating the anti-proliferative function of VPA in other tumor cell lines, including glioma (24), multiple myeloma (25), prostate (26), bladder (27), gastric (28), and urothelial (29) cancers. After VPA exposure, decreased cell proliferation in HeLa cells has been previously reported (15,30).…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that VPA significantly inhibited the proliferation of HeLa cells in a concentration-and timedependent manner. This finding is consistent with other previous studies indicating the anti-proliferative function of VPA in other tumor cell lines, including glioma (24), multiple myeloma (25), prostate (26), bladder (27), gastric (28), and urothelial (29) cancers. After VPA exposure, decreased cell proliferation in HeLa cells has been previously reported (15,30).…”
Section: Discussionsupporting
confidence: 93%
“…AdPlus-mCherry-GFP-LC3B adenovirus was also used to transfect cells, based on the principle that in the case of non-autophagy, mCherry-GFP-LC3B is present in the cytoplasm as diffuse yellow fluorescence under fluorescence microscopy, In the case of autophagy, mCherry-GFP-LC3B aggregated on the autophagosome membrane under fluorescence microscope, presenting as yellow spots; When the autophagosome and lysosome fuse, they appear as red spots due to partial quenching of GFP fluorescence. The above experimental results suggest that ursolic acid and GANT61 activate the autophagosome formation phase, but do not inhibit the lysosome fusion degradation phase [ 15 , 16 ]. Currently, hedgehog pathway inhibitors have been widely used as a treatment for various types of cancers caused by pathway overactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, known inhibitors of the Hedgehog signaling pathway include GANT61, cyclopamine, and GANT58 [ 26 ]. GANT61 specifically blocks GLI1 in the Hedgehog signaling pathway and inhibits cell transcription and expression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%